MICROBIOME AND MYCOBIOME IN CHRONIC WOUNDS - Mitrova Telenta, Julija; Dimova, Maja; Dohcheva Karajovanov, Ivana (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2023)
Skin as the biggest organ with protective function in the human body, makes an equilibrium between microbial communities and immune system. Skin microbiome is defined as the genome of microorganisms found on the skin with which microorganisms have a complex relationship. Microbiota of healthy skin consists of resident and transient microorganisms. Two most common factors for delayed healing process in chronic wounds are infection and biofilm formation. Thus, it is important to analyze microbiome and mycobiome of chronic wounds.
Keywords: microbiome; mycobiome; chronic wounds; biofilm